Money makes the wheels go round - Agarwal, O. P. (2012)
Notes that as cities expand and the world's population becomes increasingly urbanised, the need for reliable and affordable transport systems, especially in developing countries, grows more urgently. Acknowledges that with the costs of maintaining existing infrastructure and building new projects being so high, there is the need for innovative financing methods to help authorities bridge the funding gap and keep the city moving.